Nietzsche and Heidegger: truth, value and foundation - Zengotita, Alonso (2021)
Heidegger posits Nietzsche as the last metaphysician, in a line that can be traced back to Plato and who has historically displayed a cover-up of being. In this article we will seek to address Heidegger’s criticism of Nietzsche with the aim of realizing that it is sustained from a cut of the Nietzschean value-truth relation. The central hypothesis will maintain that, while Heidegger seeks to position – from the aforementioned clipping - his criticism in analytical-argumentative terms, it unfolds rather from the value that each author gives to the truth in terms of foundation.